Comparative Effectiveness of Low-Level Laser Therapy and Quantum Acoustic Waves in Patients with Chronic Low Back Pain - Sidra Shaban, Samraiz Mughal, Rehan Yaqoob, Jawad Haider, Muhammad Taha Javed, Laraib Shehzadi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Low Back pain (LBP) is a primary source of years lived with bad health condition, with an expected 70–85 percentage of the people to experience LBP at some moments in their lives. It is typically defined as backache, muscle tightness above the inferior gluteal folds and below the costal border with or without radiating pain in leg. The most prevalent issue and a major contributor to morbidity in adults is low back pain (LBP). Acute LBP is pain that lasts less than 3 months, while chronic LBP is pain that lasts more than 3 months. Nearly two thirds of adults experience it at some point in their lives. LDH, or lumbar disc herniation, is one of the most frequent causes of LBP. Objective: This study was intended to relate the effects of low-level-laser therapy and quantum acoustic waves on low-back-pain (LBP). Methods: It was a quasi-experimental study conducted at KKT orthopedic spine center and laser pain management rehab clinic, Multan from February, 2023, to April, 2023. There were two groups in total. One group was provided with low-level-laser therapy along with routine physiotherapy and the other with quantum acoustic wave along with routine physiotherapy. Assessment on 6th and 12th session was taken and measurements of Numeric Pain Rating Scale, Oswestry low back pain questionnaire and range of motion with goniometry were recorded before and after the treatment. SPSS-27 was used to analyze the data. Results: There were a total of 48 patients. 24 patients were given to low level laser group and 24 patients to quantum acoustic waves group. The mean age of patients was 30-70, Severity of pain in quantum acoustic waves group decline considerably related to low-level-laser therapy group at the end of the treatment session (p-value=<0.01). Conclusion: Mutually low-level-laser therapy and quantum acoustic waves lessens severity of pain but quantum acoustic waves caused lessening of pain severity more than low-level-laser therapy whereas, both presented major effects on range of motion ROM. Keywords: Back Disability Index; Khan Kinetic Treatment; Low level laser therapy; Low back pain